2011
DOI: 10.4049/jimmunol.1100821
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Transcriptional Machinery of the IL-8 Gene in Human Bronchial Epithelial Cells

Abstract: IL-8 released from bronchial epithelial cells infected with Pseudomonas aeruginosa plays a crucial role in the chronic lung pathology of patients affected by cystic fibrosis. Novel anti-inflammatory approaches will benefit from a thorough understanding of the regulatory mechanisms involved in the transcription of this chemokine to identify potential pharmacological targets. We addressed this issue by investigating the role of phosphoproteins and transcription factors (TFs) on transcription of IL-8 gene in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 54 publications
8
91
0
Order By: Relevance
“…A number of pathways have been found to be actively involved in the modulation of IL-8 production, including MAPKs, JAK2, and PI3K/Akt pathways (21,25,(42)(43)(44). In agreement with those studies, our results showed that the activation of ERK1/2, SAPK/JNK, p38 MAPK, JAK2, p85 PI3K, AP-1 and p65 NF-κB pathways was closely associated with the constitutive IL-8 secretion in MDA-MB-231 cells (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…A number of pathways have been found to be actively involved in the modulation of IL-8 production, including MAPKs, JAK2, and PI3K/Akt pathways (21,25,(42)(43)(44). In agreement with those studies, our results showed that the activation of ERK1/2, SAPK/JNK, p38 MAPK, JAK2, p85 PI3K, AP-1 and p65 NF-κB pathways was closely associated with the constitutive IL-8 secretion in MDA-MB-231 cells (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…PAO1 activation of Calu-3 cells is critical to trigger NF-kB activation and efficient IL-8 production (16). In this context, Cx43 has been reported to contribute to the propagation of proinflammatory signals in several epithelial cell models (9-11).…”
Section: Cx43 Does Not Regulate Il-8 Secretionmentioning
confidence: 99%
“…Another protein firmly involved in angiogenesis of neuroblastoma is vascular endothelial growth factor (VEGF) (5,6). As expected, one of the control levels is transcription-related to the interaction between IL-8 and VEGF promoters and different transcription factors, such as NF-κB, AP-1 and C-EBP/NF-IL-6 (7)(8)(9)(10)(11)(12). In addition, the expression of IL-8 and VEGF genes may be under the control of epigenetic mechanisms, such as those regulated by microRNAs in cancer, differentiation and inflammatory processes (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%